Injury profile, Biomechanical Hazards, and Holistic Health Benefits of Table Tennis: A narrative Review - Chmielnicki, Filip; Chwajta, Gabriela; Kaczor, Gabriela; Cepielik, Barbara; Cichocka, Weronika; Pirga, Gabriela; Antos, Martyna; Paczosa, Kacper; Jędruszko, Klaudia; Budzeń, Dominika (Quality in Sport, 2026)
Background: Table tennis is a dynamic, asymmetrical racket sport with low acute injury rates. However, repetitive execution of technically demanding strokes exposures athletes to significant biomechanical loading and overuse disorders. Aim: This review evaluates table tennis injury epidemiology, biomechanical mechanisms of overuse syndromes, preventive strategies, and the physical, cognitive, and neurorehabilitative benefits of participation. Materials and Methods: A narrative review was conducted using PubMed, Scopus, and Web of Science databases, focusing on contemporary studies and landmark publications relevant to injury mechanisms, prevention, and health benefits. Results: Epidemiological data show a low overall injury incidence (~3.6%, or 10 injuries per 1,000 exposure hours), with over 50% occurring during training. Repetitive topspin forehand and backhand strokes increase loading on the shoulder, upper extremity, and lumbopelvic region, contributing to overuse disorders. Prevention strategies emphasize core stability, muscular symmetry correction, eccentric strengthening, load monitoring, and recovery. Beyond competition, table tennis induces favorable cardiovascular, metabolic, and cognitive adaptations, enhancing neuroplasticity. Emerging evidence supports table tennis-based interventions for Parkinson’s disease, showing improvements in balance, motor performance, and mobility. Conclusions: Table tennis poses distinct biomechanical challenges but offers substantial health benefits. Targeted prevention is essential for competitive athletes, while recreational play serves as a safe, engaging activity supporting cognitive health and healthy aging.